Isoquercitrin and Baccharis spicata (Lam.) Baillon (Asteraceae) inflorescence extract as potential biocontrol agents against coleopteran rice weevil - Rodriguez, María V.; Campagna, María N.; Ferretti, Matías D.; Morales Ríos, Mariano G.; Martínez, María L. (Journal of Phytopathology and Disease Management, 2018)
Sitophilus oryzae L. causes significant damage during storage of agricultural products. The use of synthetic pesticides renders effective results in the short term, but has also caused pest resistance and environmental pollution. Integrated pest management programs promote the development of new pesticides from natural resources, such as those derived from plants. The objective of this work was to evaluate the insecticide activity of Baccharis spicata (Lam.) Baillon extracts and their major phenolic compounds as reduced-risk alternative substances against coleopteran rice weevil. The inflorescence methanol extract was toxic against rice weevil. Three phenolic compounds were identified in this extract by HPLC UV/DAD. Isoquercitrin showed a good toxic activity againt S. oryzae. The inflorescence methanol extract and isoquercitrin inhibited the cellulase activity on cellulose agar plate assay method, with these results and additional studies it will be possible to elucidate a mechanism of action. These findings will provide opportunities and challenges to search new botanical insecticides to control pest in stored grains.